Intercropping chili with sweet gourd at varying plant population (Bangladesh Journal of Agricultural Research, 2015)
The experiment was conducted at the experiment stations of Bangladesh Agricultural Research Institute (BARI) at Joydebpur and Jamalpur during two consecutive seasons of November 2010 to June 2012 to find out the appropriate plant population of chili (var. Manikgonj local at Joydebpur and Jamalpur local at Jamalpur ) for intercropping with sweet gourd (var. BARI Sweet gourd 2) for higher productivity and economic return. The treatments were : T1= Sole sweet gourd (2.0 m x 2.0 m), T2=Sole chili (50 cm x 40 cm), T3= Sweet gourd (100%) + chili (100%), T4= Sweet gourd (100%) + chili (60%), T5= Sweet gourd (100%) +chili (50%) and T6= Sweet gourd (100%) + Chili (40%). Averaged over the years, fruit yield of sweet gourd was reduced significantly when intercropping with more than 50% chili. Intercropping sweet gourd with chili combination (100%) + chili (40%) gave the highest sweet gourd equivalent yield (35.74 t/ha and 17.95 t/ha), gross return (Tk. 357400/ha and Tk. 179500/ha), gross margin (Tk. 274346/ha and Tk.124600/ha) and benefit cost ratio (4.30 and 3.27), respectively at Joydebpur and Jamalpur. The maximum land equivalent ratio (1.52 at Joydebpur and 1.56 at Jamalpur) was also obtained from sweet gourd (100%) + chili (40%) intercropping system. The results revealed that 40% chili population (20,000/ha) might be optimum for intercropping with sweet gourd (100%) for higher productivity and economic return. DOI: http://dx.doi.org/10.3329/bjar.v39i4.22533 Bangladesh J. Agril. Res. 39(4): 579-589, December 2014